2013
DOI: 10.1002/chem.201301535
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting and Reversing Amyloid‐β Peptide (1–40) Fibril Formation with Gramicidin S and Engineered Analogues

Abstract: In Alzheimer’s disease, amyloid‐β (Aβ) peptides aggregate into extracellular fibrillar deposits. Although these deposits may not be the prime cause of the neurodegeneration that characterizes this disease, inhibition or dissolution of amyloid fibril formation by Aβ peptides is likely to affect its development. ThT fluorescence measurements and AFM images showed that the natural antibiotic gramicidin S significantly inhibited Aβ amyloid formation in vitro and could dissolve amyloids that had formed in the absen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 49 publications
5
32
0
1
Order By: Relevance
“…The hydrophobic surface of the Janus cyclic peptide may protect the fibril-forming face of the amyloidogenic protein while the exposed hydrophilic surface inhibits fibril growth [98,102]. In agreement with other studies [81,106], targeting of hydrophobic interactions was shown to be an important aim for anti-amyloidogenic research.…”
Section: Janus Cyclic Peptidesupporting
confidence: 58%
See 3 more Smart Citations
“…The hydrophobic surface of the Janus cyclic peptide may protect the fibril-forming face of the amyloidogenic protein while the exposed hydrophilic surface inhibits fibril growth [98,102]. In agreement with other studies [81,106], targeting of hydrophobic interactions was shown to be an important aim for anti-amyloidogenic research.…”
Section: Janus Cyclic Peptidesupporting
confidence: 58%
“…Instead, molecular docking methods using the Aβ hairpin-stacked structure as amyloid model identified a possible site in which GS binds the Aβ fibril [130]. The structure of GS identified by crystallography [129] was shown to dock into the β-hairpin-like structure of Aβ(18-42) with its hydrophobic and hydrophilic residues interacting, respectively, with the apolar hydrophobic and polar hydrophilic interfaces within the amyloidogenic fibrillar tubes [106]. A family of mixed (αβαβα) 2 cyclopeptides was designed based on GS and shown to form β-hairpin-like structures [131] that fit the channel interface of Aβ better than GS, probably because of the increased flexibility [106].…”
Section: Gramicidin S and Derivativesmentioning
confidence: 98%
See 2 more Smart Citations
“…Although molecules such as ␤-sheet breakers (97) and cyclic peptides (98,99) have been devised to prevent amyloid aggregation, traditional antibodies have so far provided the best preliminary treatment results, at least for AD (100). It is unclear to what extent current amyloid inhibitors will block the formation of amyloid co-aggregates.…”
Section: Implications Of A␤ Cross-amyloid Interactionsmentioning
confidence: 99%